Sistem Pendukung Keputusan Pemilihan Laptop dengan Menerapkan Metode Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) - Sussolaikah, Kelik; Lubis, Juanda Hakim; Sallaby, Achmad Fikri; Yuliani, Ega; Mesran, Mesran (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The lack of knowledge and information regarding laptop specifications makes ordinary people who want to buy a laptop feel confused about determining which laptop suits their needs. As a tool that can be used to select a laptop, a decision support system is needed. In decision support systems there are several methods, one of which can be used is the MOORA method (Multi-Objective Optimization on the basis of Ratio Analysis). In this research, the author will raise a case to find the best alternative from predetermined criteria to determine comparisons by rating existing alternatives using the MOORA (Multi-Objective Optimization on the basis of Ratio Analysis)method. Based on the relative performance scores, Asus Rog GL552JX (A9) obtained the highest score of 0.217 and ranked first. This was followed by Asus A455LD (A4) with a score of 0.21585 and second place, and Acer Aspire E5-551 (A2) with a score of 0.19785 and third place. Acer One 10 S100X (A10) received the lowest score of 0.1042 and ranked last. Thus, Asus Rog GL552JX (A9) can be considered as the best laptop based on the established criteria in this study.